Uranyl Nitrate Hexa Hydrate Catalyzed Synthesis of pyrimidine Carboxamide Derivatives and their Biological Studies - K. Venkatesan (Current Topics on Chemistry and Biochemistry Vol. 4, 2022)
Microwave-mediated reactions have piqued the interest of organic chemists over the last two decades due to their shorter reaction times and high yields of products with high selectivity. The synthesis of pyrimidine carboxamide derivatives utilizing UO2 (NO3)2.6H2O catalyst under conventional and microwave irradiation. The use of uranyl nitrate in the synthesis of dihydropyrimidine offered various advantages, including ease of use, shorter reaction durations, and higher yields using acetonitrile as a solvent. FT-IR, 1H NMR, 13C NMR, and mass spectral data were carried out to validate the structures of the prepared compounds. All the synthesized compounds were tested for in vitro antioxidant and antibacterial activities and the results were reported.